The Impacts of Friendship, Advice and Negative Ties on Intention To Leave: The case of nurses in a special branch hospital - Cenk Sozen; Simge Samanci; Ismail Tokmak; Hakan Turgut; Nejat Basim (ACHSM, 2021)
OBJECTIVES: The high turnover rate of nurses has been a matter of debate among scholars. Nurses' social interaction patterns and the social structure they are situated within may provide clues about possible causes of their high turnover intentions. This study aims to investigate the possible effects of negative and positive ties on the intention of turnover among nurses. DESIGN & SETTING: A hybrid research methodology was used. Social network analysis was used to reveal the positions of the nurses (n = 126) in the positive and negative networks. A statistical model was formed with varying types of centrality measures, intragroup conflict, and intention to leave variables. The data was collected from all the nurses working in a special branch hospital. RESULTS AND CONCLUSION: The findings of the study clearly indicate that negative interactions directly and indirectly affect the intention to leave, and the nurses demand professional support from their colleagues. The findings also show the existence of a fragmented social structure among nurses, which suggests the increased importance of brokerage roles. Managers should closely monitor the negative interactions among nurses, and they need to use conflict management techniques frequently to reduce hostile relations in the business environment. Managers should especially seek ways to increase altruistic tendencies among colleagues because nurses demand professional support ties more than friendship relations.